Bovine serum albumin gel/polyelectrolyte complex of hyaluronic acid and chitosan based microcarriers for Sorafenib targeted delivery. Issue 34 (21st January 2020) - Paşcalău, Violeta; Tertis, Mihaela; Pall, Emoke; Suciu, Maria; Marinca, Traian; Pustan, Marius; Merie, Violeta; Rus, Iulia; Moldovan, Cristian; Topala, Tamara; Pavel, Codruta; Popa, Catalin
Abstract: The development of systems for targeted delivery of Sorafenib in unresectable hepatocellular carcinoma to reduce the systemic toxicity is a challenge. In our article, we successfully prepared core‐shell microcapsules based on bovine serum albumin gel with polyelectrolyte complex multilayer shell of polysaccharides with opposite charges, hyaluronic acid, and chitosan, encapsulating Sorafenib, as targeting delivery system for improved hepatocellular carcinoma therapy. A bovine serum albumin gel core was formed by a method based on a sacrificial CaCO3 template, followed by the multilayer shell build‐up of Ca 2+ cross‐linked hyaluronic acid hydrogel, and subsequently alternating multilayers of the polyelectrolyte complex formed between hyaluronic acid and chitosan. The following techniques: Fourier‐transform infrared and UV–Vis spectroscopy, X‐ray diffraction, differential scanning calorimetry, confocal laser scanning microscopy, atomic force microscopy, and scanning electron microscopy were used for the physicochemical characterization. These tests revealed the spherical shape of core‐shell type, the micro‐size, as well as the composition of microcapsules after their synthesis and proved the successful encapsulation and release of the drug. The promising results regarding encapsulation efficiency, Sorafenib release profile and cytotoxicity on HepG2 and mesenchymal stem cells, recommend Sorafenib loaded microcapsules as suitable targeted drug carriers for further in vivo studies for hepatocellular carcinoma therapy. Abstract : The Sorafenib release from loaded core‐shell microcapsules based on bovine serum albumin gel and multilayer shell built by the calcium cross‐linked hyaluronic acid hydrogel and the polyelectrolyte complex hyaluronic acid/chitosan in different pH buffers was studied. One can see corona formations, formed by self‐assembling of Sorafenib in the multilayer shell through interactions with the opposite charges of the polyelectrolyte complex.